Methanol leaves extract Hibiscus micranthus Linn exhibited antibacterial and wound healing activities - Berhan Begashaw; Bharat Mishra; Asegedech Tsegaw; Zewdneh Shewamene (BMC, 2017)
Abstract Background Infectious diseases are the most common causes of morbidity and mortality in developing countries. Wound and wound infections are also major health problem. Nowadays, medicinal plants play a major role in treatment of infectious diseases and wound healing and they are easily available and more affordable as compared to synthetic compounds. The aim of this study is therefore, to investigate the antibacterial and wound healing activities of 80% methanol extract of Hibiscus micranthus leaves using disc diffusion methods and rat excision model respectively. Methods In vitro antibacterial screening was carried out against S. aureus, S.pneumoniae, S. pyogenes, E. coli, P. aeruginosa, K. pneumoniae and P. mirabilis bacterial strains using disc-well diffusion assay. Would healing activity was done in rats divided into four groups each consisting of six animals. Group I was served as a negative control (ointment base), Group II served as a positive control Nitrofurazone (NFZ 0.2% ointment), Groups III and IV was treated 5 and 10% extracts respectively. The acute oral toxicity test and skin sensitivity test were also performed before conducting the actual study. The extract was analyzed for secondary metabolites using standard methods. Results Preliminary phytochemical screening have revealed the presence of alkaloids, flavonoids, saponins, tannins, steroids, phenols, diterpines, anthraquinones and the absence of glycosides, terpinoides and triterpines. Based on acute oral toxicity test the extract was found to be safe up to a dose of 2 g/kg. In addition, acute dermal toxicity test indicated no sign of skin irritation. The leaves extract exhibited varying degrees of sensitivity with zones of inhibition ranging from 14.00 ± 0.333 (S.pyogenes) to 22.67 ± 1.202 mm (S.aureus). It was found that S. aureus and S. pneumonia (p < 0.05) were the most sensitive to the extracts of the leaves at concentrations of 800 μg/ml and 400 μg/ml respectively followed by P. aeuruginosa [(18.33 ± .333 mm) (p < 0.05)] at a concentration of 400 μg/ml. However, E. coli and P. mirabilis were found to be resistant to the extract at any of the applied doses. In the wound healing study, the 5 and 10% w/w extract exhibited significant wound contraction rate of 99.30% and 99.13% as compared to NFZ ointment and simple ointment base treated groups from 6th to 16th day, respectively (p < 0.05). Conclusion The present study suggests that the methanol extract of the leaves exhibited a potential antibacterial activity against the tested microorganisms and wound healing activity.